Predictive value of plasma sICAM-1 and sP-Selectins in the risk of death in patients with acute respiratory distress syndrome - Pan, Jing; Wu, ChaoMin; Du, ChunLing; Zhou, Lei; Gu, Liang (Journal of Medical Biochemistry, 2023)
Objective: To evaluate the predictive value of sICAM-1 and sP-Selectins in the risk of death in a prospective cohort of adult acute respiratory distress syndrome (ARDS). Methods: Adult ARDS patients were included. Plasma sICAM-1, sP-Selectins, and inflammatory cytokines (TNF-α, IL-1β, IL-6, IL-8, and IL-17A) were detected in ARDS subjects. The correlation between different factors and the potential of sICAM-1 and sP-Selectins as endothelial markers to predict the risk of death from ARDS was analyzed. Results: Plasma sICAM-1 and sP-Selectins were higher in ARDS patients and higher in non-survivors of ARDS. sICAM-1 was significantly correlated with TNF-α, IL-6 and IL-8, and sP-Selectins was also significantly correlated with IL-6 and IL-8. Above the critical values of 245.5 ng/mL (sICAM-1) and 482.5 ng/mL (sP-Selectins), the death of the ARDS population increased. High plasma sICAM-1 and sP-Selectins at ICU admission were independent predictors of death of ARDS patients. Conclusion: sICAM-1 and sP-Selectins can predict the risk of death in critically ill patients with ARDS.